Effect of probiotic use on antibiotic administration among care home residents: a randomized clinical trial - Butler, CC; Lau, M; Gillespie, D; Owen-Jones, E; Lown, M; Wootton, M; Calder, PC; Bayer, AJ; Moore, M; Little, P; Davies, J; Edwards, A; et al. (American Medical Association, 2020)
Importance Probiotics are frequently used by residents in care homes (residential homes or nursing homes that provide residents with 24-hour support for personal care or nursing care), although the evidence on whether probiotics prevent infections and reduce antibiotic use in these settings is limited.